Universal remote control - Mohd Ruzaimi, Mohd Ariffin (2007)
With most pieces of consumer electronics, from camcorders to stereo equipment, an infrared remote control is usually always included. Video and audio apparatus, computers and also lighting installations nowadays often operate on infrared remote control. There are many different coding systems in use, and generally different manufacturers use different codes and different data rates for transmission. A universal remote control was developed by using C language via serial communication data transfer port. Basically, the Graphical User Interface (GUI) for the Universal Remote Control program was developed by using Microsoft Visual C++, the Microsoft application that enables the programmer to create conventional console and Windows applications. The hardware was interfaced to PC via the serial communication port. The remote can be operated on any standard TV, DVD player, satellite receiver and air-conditioner, operate over range of 15 ft, easy to use, and also reliable.